The counseling skills practice manual - Hutchinson, David R. (Thousand Oaks, Calif. SAGE, 2012)
A practical guide for students who are working on improving their counseling skills, this manual features 12 practice sessions, each of which focuses on a specific counseling skillset. Many of the essential skills are covered, such as using questions, nonverbal behaviors, making reflections of client meaning, and feeling. But the student also gains practice here with important skills, such as learning how to deal with clients in crisis and reluctant clients, how to appropriately confront, and hoe to give and receive accurate and supportive feedback to one another. These practice sessions are designed to help students recognize and build on their natural interpersonal skill set as they learn new skills. They will help students become more competent in their use of counseling skills and feel more comfortable and confident in their roles as emerging counseling professionals. Key features: Offers a comprehensive view of each skill prior to its being demonstrated; connects skills learned to professional practice ; provides ample student review and practice opportunities, including both writtent exercises and role-playing; encourages thorough evaluation ooportunities through both self-evaluation and peer/instructor evaluation.
Companion to: The essential counselor and its accompanying DVD of professionally demonstrated skills.
Keywords: Counseling psychology; Counseling -- Methodology